Gender Equality-Based Anti-Sexual Violence Islamic Boarding School at Ribatul Muta'alimin Islamic Boarding School, Pekalongan City - Yunas Derta Luluardi; Kamalludin, Iqbal; Khasna, Syarifa; Pratami, Bunga Desyana; Azami, Muhammad Fairuz Hasan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Sexual violence is increasingly massive in the educational environment, and several cases have even been recorded in Islamic boarding schools. The phenomenon of sexual violence in Islamic boarding schools has occurred several times in Central Java. Santri in this case are the weak, apart from being underage, they are also helpless with the power relations built by adults as supervisors in the pesantren, you can call them kiai, ustad, seniors or colleagues. This community service aims to increase knowledge and understanding of the academic community of Islamic boarding schools about the importance of preventing and overcoming crimes of sexual violence that occur in Islamic boarding schools. This service is carried out by introducing the problem of sexual violence that occurs in Islamic boarding schools. This is intended so that the pesantren academic community knows the legal basis for sexual violence, approaches to handling it, and institutions that can resolve sexual violence. The results of this dedication show that there is an increase in the knowledge and awareness of the pesantren academic community about their responsibilities in preventing and overcoming sexual violence crimes within the pesantren environment. The pesantren community with very high understanding increased from 10% to 65%. Meanwhile, the low understanding of the Islamic boarding school community regarding obligations and responsibilities in preventing and overcoming sexual violence crimes decreased from 50% to 10%. That all pesantren communities have the same roles and responsibilities in realizing peace and comfort in the pesantren environment.